Transient abdominal telangiectasia of the newborn: two new cases and review of the literature. - van Erp, F.; Strikvoort, L.; de Graaf, M. (European Journal of Pediatric Dermatology, 2025)
Two neonates with transient abdominal telangiectasia are presented. This relatively unknown condition is usually benign, as demonstrated by previous literature. Clinical monitoring to confirm spontaneous regression is advisable, unless other symptoms require careful pediatric evaluation and possibly abdominal imaging.